Human Vγ9Vδ2 T Lymphocytes in the Immune Response to P. falciparum Infection - Howard, Jennifer; Zaidi, Irfan; Loizon, Séverine; Mercereau-Puijalon, Odile; Déchanet-Merville, Julie; Mamani-Matsuda, Maria (Frontiers in Immunology, 2018)
Malaria is an infectious disease caused by the protozoan parasite Plasmodium sp, the most lethal being Plasmodium falciparum. Clinical malaria is associated with the asexual replication cycle of Plasmodium parasites inside the red blood cells and a dysregulated immune response. Although the mechanisms of immune responses to blood- or liver stage parasites have been extensively studied, this has not led to satisfactory leads for vaccine design. Among innate immune cells responding to infection are the non-conventional gamma-delta T-cells. The Vγ9Vδ2 T-cell subset, found only in primates, is activated in response to non-peptidic phosphoantigens produced by stressed mammalian cells or by microorganisms such as Mycobacteria, E.coli and Plasmodium. The potential protective role of Vγ9Vδ2 T-cells against infections and cancer progression is of current research interest. Vγ9Vδ2 T-cells have been shown to play a role in the early control of P. falciparum parasitemia and to influence malaria adaptive immunity via cytokine release and antigen presentation. They are activated and expanded during a primary P. falciparum infection in response to malaria phosphoantigens and their activity is modulated upon subsequent infections. Here we review the wide range of functions by which Vγ9Vδ2 T-cells could both contribute to and protect from malaria pathology, with a particular focus on their ability to induce both innate and adaptive responses. We discuss how the multifunctional roles of these T-cells could open new perspectives on gamma-delta T-cell-based interventions to prevent or cure malaria.